ENDOGENEITY OF INDONESIAN MONEY SUPPLY - Meutia Safrina Rachma (Economic Journal of Emerging Markets, 2010)
There has been a long debate about the endogeneity of money supply. The main objective of this article is to identify whether money supply in Indonesia is an exogenous or an endogenous variable. Using a Vector Autoregressive model and monthly data 1997(5)-2010(6), the estimation result shows that money supply in Indonesia is an endogenous variable. The movement of broad money supply does influence the movement of base money and Consumer Price Index. Consequently, the central bank does not have control power on money supply. The bank is only able to maintain the stability and control the movement of broad money supply. Keywords: Endogenous variable, money supply, vector autoregressionJEL classification numbers: E51, E52, E58